Locating the thing: The Antarctic as alien space in John W. Campbell's 'Who Goes There?' - Leane, E (SF-TH, Inc., 2005)
Many pulp sf writers of the early- to mid-twentieth century seized upon Antarctica as an appropriately remote and unearthly site for their magazine stories. This article focuses on one of the most famous, John W. Campbells Who Goes There?, first published in Astounding Science-Fiction in 1938, and adapted for film as The Thing in 1951 and 1982. In Campbells tale, an Antarctic expedition is devastated by a monstrous alien creature found frozen in the ice. While Who Goes There? has often been the subject of critical interest, the significance of its location has not been explored in any detail. In this article, I show how a reading focused on space and place can find new meanings in this often-examined text. Drawing on Julia Kristevas psychoanalytic theory of the abject, cultural geographer Yi-Fu Tuans notion of alien space, and a number of fictional and nonfictional Antarctic narratives, I argue that the Thing at the center of Campbells text serves as an embodiment of the continent itself.